Triple Role Overload: Working, Parenting, and Navigating Public Benefits. (August 2021) - Freeman, Amanda; Dodson, Lisa
Much has been written about work–family conflict for professional women, while little attention has focused on poor working mothers. Stuck in low-wage jobs, millions of working mothers rely on public benefits to supplement poverty wages. This article looks at the ways in which work–family–welfare conflict affected mothers' ability to maintain a stable family and work life. Using interview data and focus group data collected in Colorado, Georgia, and Massachusetts, the article uncovers the intersecting demands these mothers face and the ways in which they are ill-equipped to deal with these demands. The qualitative data are mothers' voices as they discuss the demands of parenting and work, as well as the regulations of public programs. In contrast to middle and upper-income mothers who may purchase forms of help to ease work–family tensions, poor mothers rely on government programs to offset insufficient earnings. Our findings suggest these government programs may exacerbate work–family conflict for poor mothers.